CHARACTERISTICS OF AUTISM PATIENTS IN SLB AUTISM YPPA PADANG PERIOD SEPTEMBER-NOVEMBER 2019 - R.M, Salfitri; Zeffira L; Siana Y; Wahyuni S (Sean Institute, 2022)
Autism is a brain development disorder that causes disturbances in interaction, communication and behavior. This makes people with autism often withdraw from the environment and are more likely to be alone, but children with autism have high concentration and independence with support and therapy. The aim is to find out the characteristics of people with autism in YPPA Padang Autism SLB. This type of research is descriptive research using primary data. The time of the study was carried out from September 2019 to November 2019. The sample of this study was people with autism who met the inclusion criteria, namely 49 people obtained by the Total Sampling technique. The results of the research analysis are reported in the form of a frequency distribution table. Based on the results of the study, the most age was in the 12-16 year age group (46.9%), the most gender is male (89.8%), the most parental occupations are self-employed (38.3%), making eye contact (38.3%), making appropriate facial expressions (20.4%), playing with children age (12.2%), empathize and express emotions (8.2%), habitual echolalia (26.5%), able to speak according to his developmental stage (18.4%), there are certain rituals carried out every day (59.2 %), playing toys according to function (32.7%), temper tantrum behavior (55.1%), self-harm (26.5%). Stereotypes and repetition (51%), independence (55.1%), moderate grasping power (36.7%) and concentration (59.2%). able to speak according to their developmental stage (18.4%), there are certain rituals carried out every day (59.2%), playing toys according to function (32.7%), temper tantrum behavior (55.1%), self-harm (26 ,5%). Stereotypes and repetition (51%), independence (55.1%), moderate grasping power (36.7%) and concentration (59.2%). able to speak according to their developmental stage (18.4%), there are certain rituals carried out every day (59.2%), playing toys according to function (32.7%), temper tantrum behavior (55.1%), self-harm (26 ,5%). Stereotypes and repetition (51%), independence (55.1%), moderate grasping power (36.7%) and concentration (59.2%).In this study, the most autism sufferers were men with entrepreneurial parents and there were disturbances in 3 aspects, namely disorders of social interaction, communication, and behavior.